Design of survey to evaluate the core industrial ecosystem of lean, health and safety, quality, and organisational culture - Lee, Kongting; EARL, Anna; TAYLOR, Malcolm; ZHANG, Yilei; PONS, Dirk (New Zealand Journal of Health and Safety Practice, 2024)
Context: Efficient industrial operations require the integration of lean practices, quality systems, safe methods of work, and a supportive organisational climate. Need: There is a need to manage work-related risks and ensure the safety and well-being of workers while maintaining operational efficiency and quality. While surveys exist for each of these facets and may be used to evaluate performance, there is no integrated survey of the core industrial ecosystem. Objectives: The objective was to develop a survey to measure the adoption of effective work practices- lean methodologies, the presence of health and safety in the workplace, the effectiveness of quality systems, and the role of organisational support and culture. Method: The survey combines extracts from existing surveys with new questions created to capture all the research objectives. Outcomes: A composite survey was designed to measure workers’ perspectives of lean practices, occupational and health system, quality systems, and organisational support and culture. This is original as there is no holistic survey instrument for this in the literature.